Wild Kratts. Panda-monium [videorecording (DVD)] - Kratt, Martin; Kratt, Chris
While checking out the endangered Giant panda, the Wild Kratts gets stranded in China without power to any of their vehicles. They must figure out how to 'power up' in time to help save the pandas, who are being turned into roboticized stuffed toys by the nefarious villain, Zach Varmitech. An 'ancient panda secret' just might lead to the creature power that will restart their engines and save the pandas.